LEFT BEHIND: A QUALITATIVE STUDY OF ZIMBABWEAN ADOLESCENTS AFFECTED BY PARENTAL MIGRATION - Filippa, Olga M; Cronjé, Elsje M; Ferns, Ilse (PINS-Psychology in Society, 2025)
As a result of the Zimbabwean socio-economic and political crisis many Zimbabwean parents have out-migrated, joining the diaspora in many countries leaving their children behind in the home country (Zanamwe & Devillard, 2010). Qualitative research, in the form of in-depth semi-structured interviews which were thematically analysed, was carried out with seventeen adolescents whose parents work outside Zimbabwe. Their stories, presented in this paper, give us a better idea of how these adolescents view their situation and cope with the challenges they face in their home countries. The experiences of these young Zimbabweans do not appear to be unique as they are mirrored in similar studies carried out in other parts of the world, such as Latin America and countries affected by significant out-migration. Suggestions on how the findings of the study could benefit these adolescents and directions for further research in this field conclude this study.